Mengenal Logika : Pengertian Logika, Model Logika, Jenis-jenis Logika, Macam-macam Logika, Hubungan Logika dan Ilmu Pengetahuan - Br Sitepu, Meysi Eginta; Albina, Meyniar (Cemara Education and Science, 2025)
The role of logic as a fundamental thinking tool is important in developing critical reasoning and analytical skills, especially for the younger generation. This research highlights that logical thinking skills are not only useful in academic contexts, but also in everyday life, helping individuals make rational decisions and solve problems systematically. Through logical reasoning, individuals are expected to develop a strong character, increase competitiveness, and prepare themselves to become visionary leaders with integrity.